Edukasi Dan Pelatihan Pencegahan Serta Pengelolaan Diabetes Mellitus Dan Hipertensi Pada Perwiritan Muslimat Al-Jamiatul Amaliyah Desa Lalang Sunggal Deli Serdang Tahun 2025 - Siti Khadijah Nasution; Taufik Ashar; Juanita; Tukiman; Devi Nuraini Santi (STIKES Columbia Asia Medan, 2025)
Diabetes mellitus and hypertension can be prevented through the consistent adoption of a healthy lifestyle. Women participating in religious study groups are an important segment of the community, as they play a significant role in shaping family lifestyles. A total of 30 Muslim women from the Perwiritan Muslimat Al-Jamiatul Amaliyah in Kampung Lalang, Sunggal, Deli Serdang, participated in the community service activities consisting of education and training on the prevention and management of diabetes mellitus and hypertension. The activities began with socialization of the community service program, followed by preparation by the team, including the development of educational materials and the design of pre- and post-test instruments. Based on the Wilcoxon test, the educational intervention was found to have a significant effect. This was reflected in an increase in participants’ knowledge regarding diabetes mellitus and hypertension after the intervention. Among the 30 participants, 43.3% were classified as pre-hypertensive, 40% had stage 1 hypertension, 10% experienced a hypertensive crisis, 3.3% had stage 2 hypertension, and only one participant had normal blood pressure. Of the 30 women whose fasting blood glucose levels were measured, 43.3% were classified as pre-diabetic, 23.3% had diabetes mellitus, and 33.3% had normal glucose levels. The participants expressed their hope that future activities would include cholesterol level examinations.